The effect of an acute ingestion of Turkish coffee on reaction time and time trial performance - Church, D.; Hoffman, J.; LaMonica, M.; Riffe, J.; Hoffman, M.; Baker, K.; Varanoske, A.; Wells, A.; Fukuda, D.; Stout, J. (Journal of the International Society of Sports Nutrition, 2015)
The purpose of this study was to examine the ergogenic benefits of Turkish coffee consumed an hour before exercise. In addition, metabolic, cardiovascular, and subjective measures of energy, focus and alertness were examined in healthy, recreationally active adults who were regular caffeine consumers (>200 mg per day).